Drug Packaging - Identifying, Exploring and Predicting Drug Packaging Relationships with The Environment, Customers, Manufacturers - Zbigniew WISNIEWSKI; Malgorzata WISNIEWSKA (Communications of International Proceedings, 2021)
Production and consumption of goods in highly developed countries is growing exponentially. Producers, in order to increase their sales, have to apply practices that, as a consequence, violate the stability of social-environmental-economic relations. An example of a phenomenon that has recently gained momentum in many countries is the heavy emphasis on the use of marketing influence on buyers of medicines. This is done, for example, by increasing the size of packaging while keeping the contents unchanged. This has been a long-standing practice in food production, but is different in the case of medicines. The result is an increase in packaging waste (mainly paper and aluminium contaminated with plastics), which has to be disposed of or recycled. There is a need to investigate what is the relationship between: the effectiveness of marketing activities, the product perception of drugs among customers, the environmental sensitivity of customers, the environmental effects of increasing packaging size, and the logistical effects. Logistical effects result from the intensification of logistics operations due to the need to move larger volumes of goods. This results in increased negative environmental impacts. This paper presents the background of these issues, an outline of the relationships involved, and an attempt to identify a method by which a comprehensive and multifaceted study can be conducted. A simulation modeling method will be selected to create a flexible model. The requirement for the model to be flexible is that once the relationships between its elements have been identified, it will be possible to expand its structure and scale as knowledge of the phenomena under study is gained from real situations.
Keywords: Logistics; Systems Theory; Sustainable Development; Packaging.